The tea planter's wife : a novel - Jefferies, Dinah (2016)
1920s Ceylon (now Sri Lanka). Gwendolyn, a young Englishwoman, marries Laurence, an older widower and tea plantation owner. At first Gwen finds it hard to adjust to the customs and racial issues, but on discovering she is pregnant Gwen is determined to be a good mother and a support to her husband. When Laurence's sister Verity visits, questions are raised about Laurence's first marriage and secrets about his past.
Keywords: 1505-1948; Married women -- Fiction; British -- Sri Lanka -- Fiction; Tea plantations -- Sri Lanka -- Fiction; Secrecy -- Fiction; Pregnancy -- Fiction; British; Married women; Pregnancy; Secrecy; Tea plantations; Wives -- Fiction; British -- Sri Lanka -- Fiction; Plantations -- Sri Lanka -- Fiction; Secrecy -- Fiction; Pregnancy -- Fiction; Sri Lanka -- History -- 1505-1948 -- Fiction; Sri Lanka; Sri Lanka -- History -- 20th century -- Fiction; Historical fiction; Fiction; History; Historical fiction; Historical fiction; Historical fiction